2018
DOI: 10.1534/genetics.118.301028
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of DNAase I Hypersensitive Sites in MHC Regulatory Regions of Primates

Abstract: 18It has been challenged to determine the disease-causing variant(s) for most major 19 histocompatibility complex (MHC) associated diseases. However, it is becoming increasingly 20 clear that regulatory variation is pervasive and a fundamentally important mechanism 21 governing phenotypic diversity and disease susceptibility. We leveraged DNase I data from 22 136 human cells to characterize the regulatory landscape of the MHC region, including 4867 23 DNase I hypersensitive sites (DHSs). We identified thousand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In further research, it would be interesting to extend this single-cell approach that revealed a higher percentage of decondensed MHC alleles in activated macrophages by performing DNAse1 hypersensibility assay which allows targeting the regions of chromatin that have lost their compact structure. This kind of approach has been performed to map the DNAse 1 hypersensitive regions in the MHC of Primates to determine the disease-causing variants for most major histocompatibility complex (MHC)-associated diseases [ 48 ]. Similarly, as we detected a strong overexpression of TNFα in human and porcine macrophages following LPS/IFNγ activation, a comparative study of its epigenetic profile [ 49 ] (both at the DNA methylation and histone marks levels) in resting and activated cells would further our results.…”
Section: Discussionmentioning
confidence: 99%
“…In further research, it would be interesting to extend this single-cell approach that revealed a higher percentage of decondensed MHC alleles in activated macrophages by performing DNAse1 hypersensibility assay which allows targeting the regions of chromatin that have lost their compact structure. This kind of approach has been performed to map the DNAse 1 hypersensitive regions in the MHC of Primates to determine the disease-causing variants for most major histocompatibility complex (MHC)-associated diseases [ 48 ]. Similarly, as we detected a strong overexpression of TNFα in human and porcine macrophages following LPS/IFNγ activation, a comparative study of its epigenetic profile [ 49 ] (both at the DNA methylation and histone marks levels) in resting and activated cells would further our results.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically, viruses appear to have driven ~30% of all adaptive amino acid changes in the part of the human proteome conserved within mammals (Enard et al, 2016). There is human‐chimpanzee divergence in regulatory sequences related to immune genes (He et al, 2016; Jin et al, 2018), including in microglia (brain immune cells, Xu et al, 2018), and there are human‐specific coding genes related to immunity (Costantini et al, 2019), including one expressed in microglia (Hayakawa et al, 2005). Because positive selection on immune‐related genes is common in primates (van der Lee et al, 2017), divergent evolution of immune genes could simply be due to Red Queen dynamics.…”
Section: Physiological and Genetic Evidence For Human‐specific Immune...mentioning
confidence: 99%
“…In addition to functionally annotating HARs, epigenetic data have been used to study the evolution of human gene regulation in two other ways. First, candidate regulatory elements can be generated from human data and subsequently analyzed for human variants and positive selection (15,23,31,32). A substantial minority of the resulting elements overlap previously identified HARs, but many new fast-evolving enhancers have been discovered with this strategy.…”
Section: Harsmentioning
confidence: 99%